2017
DOI: 10.1111/modl.12389
|View full text |Cite
|
Sign up to set email alerts
|

‘One Task Fits All’? The Roles of Task Complexity, Modality, and Working Memory Capacity in L2 Performance

Abstract: The present study explores the independent and interactive effects of task complexity and task modality on linguistic dimensions of second language (L2) performance and investigates how these effects are modulated by individual differences in working memory capacity. Thirty‐two intermediate learners of L2 Spanish completed less and more complex versions of the same type of argumentative task in the speaking and writing modalities. Perceived complexity questionnaires were administered as measures of cognitive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 47 publications
8
44
2
Order By: Relevance
“…Following this account, study results contribute to the growing body of evidence motivating the integration of task modality into current taxonomies of task characteristics, as advocated by several voices (e.g., Vasylets et al, 2017;Zalbidea, 2017), given its potential to influence not only focus-on-form processes (e.g., greater targetlike form incorporation) but also longer-term L2 development. More generally, findings also call attention to the utility of employing a combined process-and product-oriented perspective in L2 research seeking to unearth the role of modality, and point to the relevance of investigating and conceptualizing modality as a task feature that may hinder or boost the L2 learning opportunities that are already afforded by the cognitive demands of the task (e.g., output and input processing requirements) (e.g., Gilabert et al, 2016).…”
Section: Research Question 2: Modality Effects Salience and L2 Gramsupporting
confidence: 53%
See 1 more Smart Citation
“…Following this account, study results contribute to the growing body of evidence motivating the integration of task modality into current taxonomies of task characteristics, as advocated by several voices (e.g., Vasylets et al, 2017;Zalbidea, 2017), given its potential to influence not only focus-on-form processes (e.g., greater targetlike form incorporation) but also longer-term L2 development. More generally, findings also call attention to the utility of employing a combined process-and product-oriented perspective in L2 research seeking to unearth the role of modality, and point to the relevance of investigating and conceptualizing modality as a task feature that may hinder or boost the L2 learning opportunities that are already afforded by the cognitive demands of the task (e.g., output and input processing requirements) (e.g., Gilabert et al, 2016).…”
Section: Research Question 2: Modality Effects Salience and L2 Gramsupporting
confidence: 53%
“…Given these theoretical views, researchers in TBLT have begun to examine how modality impacts L2 production during task-based performance (e.g., Vasylets et al, 2017;Zalbidea, 2017) and how it influences the occurrence of focus-on-form processes associated with L2 learning (e.g., García Mayo & Azkarai, 2016). Yet, as highlighted by Gilabert et al (2016), empirical research that jointly considers both noticing behaviors and L2 outcomes, which can thereby inform how modality contributes to both SLA processes and products, is lacking.…”
Section: Task Modality and Affordances For L2 Grammar Developmentmentioning
confidence: 99%
“…The cognitive factor investigated in the present study, working memory, has been found to be a robust predictor of second language learning (for recent reviews, see Wen, 2016;Wen et al, 2017;Singleton, 2017), above all in studies on vocabulary and grammar learning (Sanz, Lin, Lado, Stafford & Bowden, 2014). However, few studies (Gilabert & Muñoz, 2010;Guara-Tavarés, 2013;Kormos & Safar, 2008;Kormos, 2012b;Kormos & Trebits, 2011;Mota, 2003;Tagarelli, Ruiz, Moreno & Rebuschat, 2016;Zalbidea, 2017) have examined the relationship between working memory and different dimensions of language performance, namely, complexity (both structural and lexical), accuracy and fluency (henceforth, CAF). Furthermore, these studies have come to mixed results, as will be discussed in more detail below, and they often address only one or two dimensions, with only some studies including the four dimensions of linguistic performance.…”
Section: Background Of the Studymentioning
confidence: 81%
“…This component has limited capacity and its level of involvement is determined by the executive attention demands of tasks (Conway et al, 2005). Because the central executive (henceforth executive WM) is robustly implicated in complex cognition (Baddeley, 2003), research has shown that executive abilities play a role in numerous L2 skills, including reading comprehension (e.g., Abu-Rabia, 2003), accuracy and complexity in language production (e.g., Zalbidea, 2017), and, of relevance to this study, L2 grammar development (e.g., Lado, 2017;Li et al, 2019;Serafini & Sanz, 2016). Executive WM is commonly measured using complex span tasks, such as reading or listening span tasks (Daneman & Carpenter, 1980) or an operation span task (Turner & Engle, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…cognitive demands on L2 learners (e.g., Gilabert et al, 2016;Kormos, 2014;Williams, 2012;Zalbidea, 2017). The various processes involved in oral and written communication, both of which are ever-present across L2 contexts, have been claimed to draw on differential levels of WM involvement (e.g., Gilabert et al, 2016;Grabowski, 2010;Kellogg, 2007).…”
mentioning
confidence: 99%